A comprehensive review of the supraspinal mechanisms of spinal cord stimulation on chronic pain and cognition - Gartner, Kelly E.; Rustioni, Sofia; Vohra, Aamya; Almosawi, Mustafa; Hill, Norah; Stewart, Travis; van Wouwe, Nelleke C.; Zemmar, Ajmal (Frontiers in Pain Research, 2025)
Chronic pain is one of the leading causes of disability worldwide. It can result in a significant reduction in quality of life and has been associated with decreased neurocognitive performance in attention, memory, and processing speed. Spinal cord stimulation (SCS) is a surgical treatment option for drug-refractory chronic pain. Although SCS can improve pain perception and related physical well-being, the mechanisms by which SCS improves pain perception and affects cognition remain largely unknown. Here, we review the cognitive impairments and neuroanatomical changes that can arise from chronic pain and how SCS treatment impacts these. This review identifies four key regions that may modulate attention, executive and emotional functioning, and memory with SCS: the amygdala, anterior cingulate cortex, thalamus, and somatosensory cortex. These observations suggest a role for SCS to influence and modulate the cognitive-emotional aspects of pain perception. Our review provides new insights to identify potential cortical areas that can serve as biomarkers or neuromodulation targets for SCS treatment. Recognizing the changes in activity within these supraspinal regions during SCS treatment may help individualize pain treatment and induce favorable cognitive shifts.